Estimation of Mass Input in the Shirase and the Soya Drainage Basins in Mizuho Plateau - Yamada, T.; Watanabe, O. (1978)
P(論文) The amount of mass input was estimated for the Shirase and the Soya drainage basins in Mizuho Plateau, East Antarctica, using the data of surface mass balance, obtained by means of the snow stake measurement and the stratigraphic analysis performed over seven years from 1968 to 1974 in consideration of the regional characteristics of the balance as a function of elevation, the influences of the topography of the ice sheet on the balance and the annual variations of the balance. The Shirase and the Soya drainage basins are, respectively, 200×(10)^3 and 22×(10)^3(km)^2 in area; 20.8 and 5.9 Gta^<-1> in estimated maximum mass input; 4.6 and 0.1 Gta^<-1> in estimated minimum mass input; 12.7 and 3.0 Gta^<-1> in hypothetic average of mass input, which correspond to 64 and 150(kgm)^<-2>a^<-1> in balance. departmental bulletin paper